Double blind, placebo controlled trial of metronidazole in Crohn's disease. Issue 9 (September 1991) - Sutherland, L; Singleton, J; Sessions, J; Hanauer, S; Krawitt, E; Rankin, G; Summers, R; Mekhjian, H; Greenberger, N; Kelly, M
Abstract : A double blind study compared the efficacy of metronidazole in two doses (20 mg/kg, 10 mg/kg) with placebo in patients with Crohn's disease. One hundred and five patients participated but only 56 completed the 16 week study -21 were withdrawn for deterioration of symptoms, 17 for adverse experiences, and 11 for protocol violation. Significant improvement in disease activity as measured by the Crohn's disease activity index (metronidazole 20 mg/kg, 97 units; metronidazole 10 mg/kg, 67 units; placebo -1 unit, p = 0.002) and serum orosomucoid (metronidazole 20 mg/kg/day, 49; 10 mg/kg/day, 38; placebo, -9, p = 0.001)) were detected. Changes in C reactive protein concentrations did not achieve significance when all three groups were considered but were significant when all metronidazole treated patients were grouped and compared with the placebo treated patients (0.8 v -0.9, p less than 0.05). Although patients receiving metronidazole 20 mg/kg/day had a greater improvement in disease activity than those receiving 10 mg/kg/day (difference 30 units (95% confidence intervals -27-87), the small sample size may have precluded the detection of statistical significance. Preliminary analysis suggests that metronidazole was more effective in patients with disease confined to the large intestine or affecting both small and large bowel than in those with small bowel disease only. There were no differences in remission rates between metronidazole and placebo treated patients. We conclude that metronidazole warrants further assessment in the treatment of patients with active Crohn's disease.